Platelet depletion does not alter the course of Brucella abortus infection in vivo - Arias Gómez, Berny (2022)
Brucellosis is a bacterial disease of animals and a zoonotic infection. Thrombocytopenia is a common outcome in long-lasting brucellosis in humans. Likewise, ex vivo experiments have shown that platelets may play a role in Brucella abortus infections. Following these reports, we explored the course of brucellosis in thrombocytopenic mice, using the non-toxic low-molecular-weight aspercetin protein that depletes platelets in vivo. Aspercetin does not induce systemic hemorrhage or inflammation, and when injected into mice, it generates a rapid dose- dependent drop in platelet counts without affecting central organs, disrupting hematological parameters, or the proinflammatory cytokine profile. Compared to the B. abortus infected control group, the infected throm- bocytopenic mice did not show significant differences in the hematological profiles, pathological score, spleen, liver histopathology, or bacterial loads. Except for IL-6, which was higher in the infected thrombocytopenic mice, the TNF-α, IFN-γ and IL-10 did not significantly differ with the PBS-infected group. The results indicate that platelets do not play a significant role in modulating Brucella infection in vivo at the early stages of infection, which is commensurate with the stealthy strategy followed by Brucella organisms at the onset of the disease.